2011
DOI: 10.1186/1750-1172-6-54
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the impact of 1q21.1 copy number variant

Abstract: Background1q21.1 Copy Number Variant (CNV) is associated with a highly variable phenotype ranging from congenital anomalies, learning deficits/intellectual disability (ID), to a normal phenotype. Hence, the clinical significance of this CNV can be difficult to evaluate. Here we described the consequences of the 1q21.1 CNV on genome-wide gene expression and function of selected candidate genes within 1q21.1 using cell lines from clinically well described subjects.Methods and ResultsEight subjects from 3 familie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
51
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 51 publications
(55 citation statements)
references
References 41 publications
2
51
0
2
Order By: Relevance
“…While deletions and duplications of specific loci may yield drastically different phenotypes, the contradictory observation of both deletions and duplications leading to similar phenotypes is also common. This may be explained by the general sensitivity of certain cellular functions to dosage imbalance, such as that observed for the 1q21.1 region [Harvard et al, 2011]. This model is also supported in an alternative gene context by Auerbach et al [2011], who recently demonstrated that fragile X and tuberous sclerosis mouse models affect the same pathway (glutamate receptor 5) in opposite directions with both disruptions resulting in syndromic autism and ID features.…”
Section: Variable Expressivity Of Specific Locimentioning
confidence: 83%
See 1 more Smart Citation
“…While deletions and duplications of specific loci may yield drastically different phenotypes, the contradictory observation of both deletions and duplications leading to similar phenotypes is also common. This may be explained by the general sensitivity of certain cellular functions to dosage imbalance, such as that observed for the 1q21.1 region [Harvard et al, 2011]. This model is also supported in an alternative gene context by Auerbach et al [2011], who recently demonstrated that fragile X and tuberous sclerosis mouse models affect the same pathway (glutamate receptor 5) in opposite directions with both disruptions resulting in syndromic autism and ID features.…”
Section: Variable Expressivity Of Specific Locimentioning
confidence: 83%
“…The commonalities and differences between duplication and deletion phenotypes may be explained, in part, by the variable dosage sensitivity of the genes contained in the CNV region. To this end, Harvard et al [2011] performed functional analyses on two genes with a strong correlation between expression levels and copy number state. In a cell model the authors observed that one gene (CHD1L) demonstrated a functional deficit under both over-and underexpression conditions, while another gene (PRKAB2) only affected its associated functions in a deletion state.…”
Section: Variable Expressivity Of Specific Locimentioning
confidence: 99%
“…1,2,[5][6][7][8][9][10][11][12] We also examined primary articles and reviews of CNVs in autism, 13 schizophrenia, 14 mental retardation, 15 and congenital heart disease 16 for references to studies reporting subjects with 1q21.1 duplications. [17][18][19][20] Other citations involving 1q21.1 duplication cases were also assessed.…”
Section: Materials and Methods Literature Reviewmentioning
confidence: 99%
“…3,35 We systematically reviewed 28 primary reports identified and their accompanying supplemental materials to identify unique individuals and abstract as much information as possible on each subject. 1,2,[5][6][7][8][9][10][11][12][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34] Any subjects with 1q21.1 duplications that were not 1.0-5.0 Mb (Figure 1) in size were excluded, 12,31 allowing us to include atypical variants that were larger or smaller than the standard duplication classes used in our analyses. We documented the ascertainment criteria, country of origin, authors, and the demographic, clinical, and genotypic characteristics of subjects in different studies, and used these variables to attempt to identify duplicate cases reported in two or more papers.…”
Section: Materials and Methods Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation